Resting‐State Brain Amplitude of Low‐Frequency Fluctuations: A Comparative Study Across Different Frequency Bands in Student Pilots - Ye, Lu; Yu, Xinli; Yan, Dongfeng; Ma, Shan (Journal of neuroscience research, 2025)
ABSTRACT In this study, we aimed to investigate changes in the mean amplitude of low‐frequency fluctuations (mALFF) in different frequency bands in flight trainees using resting‐state functional magnetic resonance imaging (rs‐fMRI) technology to explore the impact of flight training on brain functional changes. The study included 39 flight trainees and 37 well‐matched healthy controls. MATLAB software was used to perform two‐sample t‐tests on the mALFF values of the subjects in different frequency bands to identify intergroup differences. SPSS software was used to perform correlation analysis between the different brain areas and the results of the Berg Card Sorting Test (BCST). The results revealed significant differences in mALFF values in multiple brain areas, including the left medial superior frontal gyrus and the left postcentral gyrus, between the two groups. Sub‐bands revealed more differential brain areas compared to the classical band, and these differential brain areas were significantly correlated with the total accuracy of the BCST. Under resting conditions, flight trainees who underwent flight training showed significant differences from the control group in brain regions related to cognitive executive control, somatosensory function, memory function, and other functions. This may be related to the learning of critical flight skills, such as emergency operations, maneuvering the aircraft for takeoff, landing, and re‐flight during executive flight training. Meanwhile, the sub‐band is more sensitive to information about brain functional activities than the classical band, which provides a new perspective for further exploring the changes in pilot brain functional mechanisms in the future. In our study, we selected pilot trainees as subjects and utilized resting‐state functional magnetic resonance imaging (rs‐fMRI) to analyze the impact of flight training on their brains. After examining the correlations between classical and sub‐band brain regions and behavioral tests, we discovered that flight training induced changes in the superior frontal gyrus, posterior central gyrus, fusiform gyrus, and middle occipital gyrus of the pilot trainees' brains.